Comparative analysis of torque-adding wind energy conversion systems with a counter-rotating vs. conventional electric generator - Saulescu, Radu; Jaliu, Codruta; Neagoe, Mircea; Ciobanu, Daniela; Cretescu, Nadia (Frontiers in Energy Research, 2023)
The paper presents a comparative analysis on the steady-state behavior of two counter-rotating wind turbines with same components, where the generator can operate as a counter-rotating (with both a mobile rotor and stator—Case a) vs. conventional (with a fixed stator—Case b) electric machine. These wind energy conversion systems (WECSs) also have two coaxial counter-rotating wind rotors and a one-degree-of-freedom (1-DOF) planetary speed increaser with two inputs and one or two outputs for compatibility with the considered generator. The paper aims at highlighting the efficiency and energy performances of WECSs with a counter-rotating vs. conventional generator by investigating three functional scenarios (A, B, and C) of the two WECS cases (a and b) under the assumption of identical or different counter-rotating wind rotors. A generalized kinetostatic modeling algorithm is first proposed, starting from the general case of WECS with a counter-rotating generator, which allows the establishment of analytical relationships corresponding to speeds and torques at input and output shafts. Numerical simulations of the obtained closed-form model in each scenario highlighted the influence of the constructive parameters on WECS performances, as well as the energetic superiority of WECS, with a counter-rotating generator (Case a) vs. conventional generator (Case b): higher efficiency by 1.2% and more output power by 1% (Scenario A) to 5.5% (Scenario C).